MMPs Regulate Neuronal Substance P After a Painful Equibiaxial Stretch in a Co-Culture Collagen Gel Model Simulating Injury of an Innervated Ligament - Ita, Meagan E.; Winkelstein, Beth A. (Frontiers in Mechanical Engineering, 2022)
Chronic joint pain is a major health problem that can result from abnormal loading of the innervated ligamentous capsule that surrounds synovial joints. The matrix metalloproteinases-1 (MMP-1) and MMP-9 are hypothesized pain mediators from stretch-induced injury since they increase in pathologic joint tissues and are implicated in biomechanical and nociceptive pathways that underly painful joint injuries. There also is emerging evidence that MMP-1 and MMP-9 have mechanistic interactions with the nociceptive neuropeptide substance P. Yet, how ligament stretch induces painful responses during sub-failure loading and whether MMP-1 or MMP-9 modulate nociception via substance P is unknown. We used a neuron-fibroblast co-culture collagen gel model of the capsular ligament to test whether sub-failure equibiaxial stretch above the magnitude for initiating nociceptive responses in neurons also regulates MMP-1 and MMP-9. Pre-stretch treatment with the MMP inhibitor ilomastat also tested whether inhibiting MMPs attenuates the stretch-induced nociceptive responses. Because of the role of MMPs in collagen remodeling, collagen microstructural kinematics were measured in all tests. Co-culture gels were incubated for one week in either normal conditions, with five days of ilomastat treatment, or with five days of a vehicle control solution before a planar equibiaxial stretch that imposed strains at magnitudes that induce pain in vivo and increase nociceptive modulators in vitro. Force, displacement, and strain were measured, and polarized light imaging captured collagen fiber kinematics during loading. At 24 hours post-stretch, immunolabeling quantified substance P, MMP-1, and MMP-9 protein expression. The same sub-failure equibiaxial stretch was imposed on all co-cultures, inducing a significant reorganization of collagen fibers (p≤0.031) indicative of fiber realignment. Stretch induces a doubling of substance P expression in normal and vehicle-treated co-cultures (p=0.038) that is prevented with ilomastat treatment (p=0.114). Although MMP-1 and MMP-9 expression are unaffected by stretch in all co-culture groups, ilomastat treatment abolishes the correlative relationships between MMP-1 and substance P (p=0.002; R2=0.13) and between MMP-1 and MMP-9 (p=0.007; R2=0.11) that are detected without inhibitor. Collectively, these findings implicate MMPs in painful ligamentous injury and contribute to a growing body of work linking MMPs to nociceptive-related signaling pathways and/or pain.